Inhibicija korozijskih procesov - Kosec, Tadeja (Vakuumist, 2006)
Many materials, especially metals and its alloys, are prone to deteriorate in its natural environment. Thermodynamics of such process can be slowed down with the addition of inhibitors. Different inhibitors, its choice and action is discussed. Laboratory electrochemical testing of inhibition of copper by benzotriazole is studied and shown.